Development of a method for the speciation of mercury in environmental sample analysis (Pembangunan kaedah bagi analisis penspesian merkuri dalam sampel analysis) - Rahman, Md. Mokhlesur; Awang, Mohamed; Mohd Yusof, Alias; Wood, Abdullah Khalik; Hamzah, Mohd Suhaimi; Abd. Rahman, Shamsiah (Malaysian Society of Analytical Sciences (ANALIS), UKM, 2012)
Trace concentrations of mercury in water samples were determined by a method involving a simple and rapid procedure connecting the flow-injection inductively coupled plasma mass spectrometry (FI-ICP-MS) and graphite furnace atomic absorption spectrometry (GFAAS) techniques. Mercury vapor, generated by sodium borohydride as the reductant, was stabilized by potassium dichromate (K2Cr2O7), then released by controlled heating and detected by FI-ICP-MS. A flow injection sample introduction system with time based injection was used and the sensitivity was found to be proportional to the mass of mercury introduced. Methyl mercury(II) was preconcentrated using the ammonium pyrrolidine dithiocarbamate (APDTC)-chloroform extraction procedure and the chloroform extract was introduced into the graphite tube. A linear calibration graph was obtained for 5-150 ng mercury in 2.5 ml of chloroform extract. Because of the high stability of MeHg(II)-APDTC complexes, it is possible to evaporate the extract in order to obtain a crystalline powder to be dissolved with a few micro liters of chloroform enacting MeHg(II) and Hg(II) can be detected at sub-nanogram levels.